2022
DOI: 10.1177/19386400221136591
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Replacement Outcome in Patients With Inflammatory Versus Noninflammatory Arthritis: A Systematic Review and Meta-analysis

Abstract: Background The decision regarding total ankle replacement (TAR) is challenging in patients with inflammatory arthritis (IA) regarding more inferior bone quality, large bone cysts, and increased risk of infections. This systematic review and meta-analysis aimed to compare the functional outcome, revision rate, complication rate, and survival rate of TAR between IA (including rheumatoid arthritis [RA]) and noninflammatory arthritis (NIA) (primary and posttraumatic). Methods After reviewing the full texts, 30 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Notably, Ling et al also did not find a significant correlation between chronic steroid use and superficial SSI or wound dehiscence [ 18 ]. Additionally, our findings are consistent with a recent meta-analysis and systematic review conducted by Mousavian et al, which demonstrated comparable complication rates between inflammatory and noninflammatory arthritis patients undergoing TAA [ 24 ]. This meta-analysis supports our conclusion that TAA is a safe and effective procedure in patients who may be taking chronic steroids for inflammatory arthritis.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, Ling et al also did not find a significant correlation between chronic steroid use and superficial SSI or wound dehiscence [ 18 ]. Additionally, our findings are consistent with a recent meta-analysis and systematic review conducted by Mousavian et al, which demonstrated comparable complication rates between inflammatory and noninflammatory arthritis patients undergoing TAA [ 24 ]. This meta-analysis supports our conclusion that TAA is a safe and effective procedure in patients who may be taking chronic steroids for inflammatory arthritis.…”
Section: Discussionsupporting
confidence: 92%
“…Post-surgical iatrogenic effects have also been described, such as: ankylosis in the midfoot [ 59 ], increase in rearfoot varus, and increased forefoot stiffness, failed total ankle arthroplasty leading to arthrodesis of the ankle [ 60 ]. However, in a recent meta-analysis, it has been concluded that total ankle replacement is a safe procedure for RA patients with difficulties close to other reasons for ankle replacement [ 61 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%